The role of block chain in protecting financial data - Mohammed, Majeed Mohsen (Technium Social Sciences Journal, 2025)
This study discusses the basic components in the field of block chain by studying two main variables: the block chain (asymmetric encryption key, transactions, consensus mechanism between nodes) as an independent variable and financial data protection as a dependent variable. This study provides a vision, forecast, and evaluation of the best economic conditions and company performance in the future In addition, this study aims to help users and developers through the application programming interface, allowing them to easily replicate data through the blockchain and Its impact on financial data.